Sistem Pendukung Keputusan Penentuan Penerima Beras Raskin Di Desa Pearaja Kecamatan Sorkam Kota Sibolga Dengan Metode Preference Selection Indeks (PSI) - Yanti Rutmana Gultom (Bulletin of Information System Research, 2023)
Rice for poor families or Raskin is a government program in tackling poverty. The Raskin program aims to help the poor and vulnerable groups to get enough food and carbohydrates without being constrained. However, in the implementation of the Raskin, there are many problems, one of which is the distribution of rice that is not targeted, to overcome a problem, a study was made to develop computer applications that help make decisions. Distribution of Raskin must be carried out properly, transparently and organized so that the Raskin received is right on target and really people in need. Therefore, a decision support system is needed to assist officers in selecting residents who are entitled to receive Raskin assistance based on predetermined criteria. The decision support system method used in making this decision is the Preference Selection Index (PSI) method. The Decision Support System for Raskin Rice Recipients in Pearaja Village, Sorkam District, Sibol City by using the Preference Selection Index (PSI) method provides convenience in processing data and making decisions to determine families who are unable and entitled to receive Raskin assistance and ease in making reports for Raskin recipients.